POG MARKETING EFFICIENCY IN THE FRAMEWORK OF INCREASING FARMERS' INCOME (Case Study at UD. Moleh Farm Animal Husbandry, Jagapati Village, Abiansemal District, Badung Regency) - D., Chandra; Putri, B. R. T.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the marketing efficiency of pigs to increase farmers' income (a case study at UD. Moleh Farm Animal Husbandry, Jagapati Village, Abiansemal District, Badung Regency). The research method used is qualitative and quantitative. The selection of farmer respondents using the stratified sampling method consisted of owners and workers at UD. Moleh Farm, wholesalers, and direct consumers. The data used are primary data and secondary data. This research was conducted from September to November 2021. The data analysis used was an analysis of marketing channels, marketing margins, Farmer's share, and marketing efficiency. The results of the research showed the marketing pattern for pigs at UD. Moleh Farm, Jagapati Village, Abiansemal District, Badung Regency consists of two marketing channel patterns, namely (I) Farmer-Consumer, (II) Farmer-Trader Collector-Consumer. The highest margin is in marketing channel II, which is Rp. 220,000/head while the lowest margin is in marketing channel I because it does not involve intermediary traders because the price at the consumer level is the same as the price at the breeder level. In addition, research data shows that the first marketing channel is the most efficient and is recommended in this study because it has the highest Farmer Share value of 100%.